Students’ School-Based Assessment Scores Relationship with Students’ Readiness, Motivation, and National Examination Scores of Mathematics Subject - Furintasari Setya Astuti; Heri Retnawati (JPP (Jurnal Pendidikan dan Pembelajaran), 2017)
The aim of this current research was to know the relationship between students’ scores from the school-based assessment and their readiness, motivation, and national examination scores. The method of this research was survey. The study involved 364 students from some of senior high schools in Ngawi. The data were analyzed using path analysis. There were four students who were considered outliers and should therefore be excluded in the study, resulting in the final data from 360 students. The results of this research showed that there was a direct relationship between students’ scores from the school-based assessment with students’ motivation and their scores in national examination, but there was no relationship between the school-based scores with students’ readiness. In addition, there was an indirect relationship between motivation and school-based scores with readiness. The research also indicated that there was a negative correlation between school-based scores with readiness, motivation, and students’ scores in the national examination in mathematics.